Cocaine-Induced Breakdown of the Blood-Brain Barrier and Neurotoxicity - Sharma H.S.; Muresanu D.; Sharma A.; Patnaik R. (My University, 2025)
Role of cocaine in influencing blood-brain barrier (BBB) function is still unknown. Available evidences suggest that cocaine administration results in acute hyperthermia and alterations in brain serotonin metabolism. Since hyperthermia is capable to induce the breakdown of the BBB either directly or through altered serotonin metabolism, a possibility exists that cocaine may induce neurotoxicity by causing BBB disruption. This hypothesis is discussed in this review largely based on our own laboratory investigations. Our observations in rats demonstrate that cocaine depending on the dose and routes of administration induces profound hyperthermia, increased plasma and brain serotonin levels leading to BBB breakdown and brain edema formation. Furthermore, cocaine was able to enhance cellular stress as seen by upregulation of heat shock protein (HSP 72 kD) expression and resulted in marked neuronal and glial cell damages at the time of the BBB dysfunction. Taken together, these observations are the first to suggest that cocaine-induced BBB disruption is instrumental in precipitating brain pathology. The possible mechanisms of cocaine-induced BBB breakdown and neurotoxicity are discussed. © 2009 Elsevier Inc. All rights reserved.